SN 2018hti: a nearby superluminous supernova discovered in a metal-poor galaxy. Issue 1 (6th July 2020) - Lin, W L; Wang, X F; Li, W X; Zhang, J J; Mo, J; Sai, H N; Zhang, X H; Filippenko, A V; Zheng, W K; Brink, T G; Baron, E; DerKacy, J M; et al.
ABSTRACT: SN 2018hti is a Type I superluminous supernova (SLSN I) with an absolute g -band magnitude of −22.2 at maximum brightness, discovered by the Asteroid Terrestrial-impact Last Alert System in a metal-poor galaxy at a redshift of 0.0612. We present extensive photometric and spectroscopic observations of this supernova, covering the phases from ∼−35 d to more than +340 d from the r -band maximum. Combining our BVgri -band photometry with Swift UVOT optical/ultraviolet photometry, we calculated the peak luminosity as ∼3.5 × 10 44 erg s −1 . Modelling the observed light curve reveals that the luminosity evolution of SN 2018hti can be produced by an ejecta mass of 5.8 M⊙ and a magnetar with a magnetic field of B = 1.8 × 10 13 G having an initial spin period of P 0 = 1.8 ms. Based on such a magnetar-powered scenario and a larger sample, a correlation between the spin of the magnetar and the kinetic energy of the ejecta can be inferred for most SLSNe I, suggesting a self-consistent scenario. Like for other SLSNe I, the host galaxy of SN 2018hti is found to be relatively faint ( Mg = −17.75 mag) and of low metallicity ( Z = 0.3 Z⊙ ), with a star formation rate of 0.3 M⊙ yr −1 . According to simulation results of single-star evolution, SN 2018hti could originate from a massive, metal-poor star with a zero-age main sequence (ZAMS) mass of 25–40 M⊙, or from a less massive rotating star with M ZAMS ≈ 16–25 M⊙ . For the case of a binary system, its progenitor could also be a star with $M_ZAMS \gtrsim 25\, M_\odot$ .